PENYELESAIAN TINDAK PIDANA RINGAN TERHADAP HARTA KEKAYAAN MELALUI KEADILAN RESTORATIF BERDASARKAN TEORI PENCEGAHAN KEJAHATAN - Supyanto, Heri; Lay, Jemi; Kuntardjo, Carolina (Jurnal Magister Hukum Perspektif, 2024)
Light crimes have been regulated in a limited manner in Indonesia in the Criminal Code (KUHP). The category includes violations that carry a maximum penalty of imprisonment of three months or a fine. However, minor crimes related to wealth are experiencing problems, along with the implementation of restorative justice. Therefore, there are 2 problems in this article, namely: (1) What is the deliberation model at the Sector Police Headquarters in resolving minor crimes related to assets based on restorative justice? (2) How do Sector Police members supervise the implementation of the parties' agreement to encourage the achievement of the goals of restorative justice? This legal research method is empirical with a criminological juridical approach. Research results: (1) The deliberation model at the Sector Police Headquarters in resolving minor crimes related to wealth is based on restorative justice using a deliberation model between the perpetrator and the victim with the principle of kinship. (2) How members of the Sector Police carry out supervision over the implementation of the agreement between the parties in order to encourage the achievement of the goals of equitable restorative justice. Investigators carry out investigations and act as mediators in the context of monitoring and implementing agreements between the parties that encourage the achievement of restorative justice. Keywords: minor crimes, wealth, restorative justice, crime prevention theory